2011
DOI: 10.1007/s12185-011-0805-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioning by fludarabine/busulfan without additional irradiation or T-cell depletion leads to low non-relapse mortality in unrelated bone marrow transplantation

Abstract: In reduced intensity, allogeneic stem cell transplantation from unrelated donors (u-RIST), graft-versus-host disease (GVHD), graft failure, and non-relapse mortality (NRM) are persistent problems. Although anti-thymocyte globulin, alemtuzumab, and total body irradiation (TBI) have been explored as conditioning modalities for u-RIST, the necessity for T-cell depletion or TBI to prevent GVHD or facilitate engraftment in u-RIST has not been determined. We here report the use of u-RIST with bone marrow grafting, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…A total of 20 were included based on the strict selection criteria outlined and were categorized according to conditioning regimen or GVHD prophylaxis (Tables 3-7). Seven of these studies included regimens that fit with more than 1 of our predefined categories [22][23][24]26,28,30,32] and 2 of these studies [23,26] included regimens that fell under 3 of our categories. Because of the lack of randomized controlled trials focusing on OM as the primary outcome and heterogeneity of scales used to measure OM, a meta-analysis could not be performed; however, pooled analysis indicated significant differences in incidence of OM with respect to different conditioning regimens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 20 were included based on the strict selection criteria outlined and were categorized according to conditioning regimen or GVHD prophylaxis (Tables 3-7). Seven of these studies included regimens that fit with more than 1 of our predefined categories [22][23][24]26,28,30,32] and 2 of these studies [23,26] included regimens that fell under 3 of our categories. Because of the lack of randomized controlled trials focusing on OM as the primary outcome and heterogeneity of scales used to measure OM, a meta-analysis could not be performed; however, pooled analysis indicated significant differences in incidence of OM with respect to different conditioning regimens.…”
Section: Resultsmentioning
confidence: 99%
“…We intended to conduct a meta-analysis; however, given the number of studies that focused on OM as a secondary outcome and the variety of scales used to analyze OM incidence, we instead performed a systematic review. None of the studies included information on prior radiation therapy, though some studies included patients who had received previous chemotherapy or transplantation [27,30,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined treatment with CUR may allow a reduction in the clinical dose of BUS for HSCT, with the potential for reducing NRM. Nakane et al showed that reduced-intensity conditioning by BUS was associated with lower NRM in patients undergoing unrelated bone marrow transplantation [ 40 ]. The results of the current study showed a significant reduction in the percentage of cells in G0/G1 phase in the combination group ( Figure 4(d) ), suggesting that cells in G0/G1 phase were more sensitive to this drug combination.…”
Section: Discussionmentioning
confidence: 99%